Untimely meditations for critical pedagogy. Issue 1 (1st January 2020) - Hattam, Robert
ABSTRACT: Unfortunately our times are characterised by a serious dissonance between the logic of education policy and the challenges of the nation. In this context, we need to continue to reinvigorate critical pedagogy studies, both theoretically and practically. But to diagnose the times, following Nietzsche, we need untimely meditations – we need to ensure that we neither perfectly coincide with it, nor adjust ourselves to its demands, but instead we adhere to it whilst keeping a distance from it. This paper takes up the task of rethinking critical pedagogy through affect studies. There are multiple reasonings for the "affective turn" that are of interest here, including the critiques of the Cartesian subject and its claims to Reason, and that lots of the action (experience) has little to do with rationality per se, but instead occurs on a "terrain of affect". Put simply, critical pedagogy studies too often privileges making the better the argument, instead of engaging our capacities for affecting or being affected. The paper rehearses two recent attempts to think critical pedagogy through affect: remembrance learning, and sensation(al) pedagogies. The paper concludes with a short list of strategies.